ANALISIS SIKAP PEMBELIAN DAN KEPUASAN KONSUMEN TERHADAP ATRIBUT PRODUK IKAN KALENG DI KECAMATAN RUNGKUT KOTA SURABAYA - Devy, Listia (Berkala Ilmiah AGRIDEVINA, 2019)
The continued development of the food industry led to a lot of food production very practical, economical, attractive and durable eg food packaged in cans, it caused many consumers are interested to consume so that the production of canned food is increasing. The purpose of this study are: (1) To identify the characteristics of consumers in considering the brand and product attributes Canned Fish purchased (2) to analyze the attitude of Figures Ideal consumers to attribute Products Canned Fish (3) to analyze the level of customer satisfaction Products canned fish. East Java Province. In this study using purposive sampling method (deliberately) that sampling based on specific criteria or considerations, appropriate research purposes. Data analysis methods used in this research is descriptive analysis with the help of descriptive tabulations, method of Ideal Point Model Analysis, and Customer Satisfaction Index (CSI). Ideal attributes include attributes according to consumer prices, Clarity Expiration Date, Brand Canned Condition, Nutritional content, size Saji, Varean Rasa, as well as the Department of Health and MUI Permit for the result that the average gap or no more than 1, which means that atrbut- Canned Fish Products attributes are already close to the ideal or desired in accordance with the consumer. Attributes that result is not ideal that the attributes of packaging design and composition because there is a gap of more than 1. Value Customer Satisfaction Index (CSI) is approximately 0.674, or 67.4%, which means consumers are satisfied in buying the canned fish products DOI : https://doi.org/10.33005/adv.v8i1.1613